Effective synthesis of patterned polymer brushes with tailored multiple graft densities - Wang, Chen-Gang (2020)
This paper reports an effective method to prepare patterned polymer brushes on surfaces with tailored graft densities. High-density (concentrated), moderate-density (semidiluted), and low-density (diluted) polymer brushes were fabricated in patterned manners, offering defined three-dimensional patterned structures. This method uses a middle/near-UV (≥250 nm) lamp and needs only a short time (≤10 min) to fabricate prepatterns of the initiator, in sharp contrast to the previous high-energy lithography and time-consuming processes. The obtained patterned brush served as a molecular (protein) repellent/adsorptive interface based on a graft-density-dependent size-exclusion effect. This method is facile and accessible to wide ranges of tunable density and pattern shapes, which are attractive for extensive use.